Party patronage in contemporary democracies: results from an expert survey in 22 countries from five regions - Kopecky, Petr; Meyer Sahling, Jan-Hinrik; Panizza, Francisco; Scherlis, Gerardo; Schuster, Christian; Spirova, Maria (Wiley, 2016)
This Research Note presents a new dataset of party patronage in 22 countries from five regions. The data was collected based on the same methodology to compare patterns of patronage within countries, across countries and across world regions that are usually studied separately. The Note addresses three research questions that are at the center of debates on party patronage, which is understood as the power of political parties to make appointments to the public and semi-public sector: the scope of patronage, the underlying motivations, and the criteria on the basis of which appointees are selected. The exploration of the dataset shows that party patronage is, to a different degree, widespread across all regions. The data further shows differences between policy areas, types of institutions such as government ministries, agencies and state-owned enterprises, and higher, middle and lower ranks of the bureaucracy. It is demonstrated that the political control of policy-making and implementation is the most common motivation for making political appointments. However, in countries with a large scope of patronage, appointments serve the purpose of both political control and rewarding supporters in exchange for votes and services. Finally, the data shows that parties prefer to select appointees who are characterized by political and personal loyalty as well as professional competence.